Maduración ovárica en la "mosca de la guayaba" Anastrepha striata Schiner (Diptera: Tephritidae) - Ramírez Cruz, Arturo; Hernández Ortiz, Vicente; Martínez M, Imelda (Instituto de Ecología, A.C., 1969)
There are many protected areas in Oaxaca. And many others with disturbed, nevertheless, it is imperative to effectively areas in the Sierra Madre de Oaxaca the Isthmus of Tehuantepec: and the Sierra Madie del Sur, especialy at elevations between sea level and 1000 m for diversity and between 1200 and 2600 m for endemism.